The Hasidic parable - Wineman, Aryeh (Jewish Publication Society, 2001)
"The teachers of Hasidism gave new life to the literary tradition of parable, a story that teaches a spiritual or moral truth. In The Hasidic Parable, acclaimed author Aryeh Wineman takes readers through the great works of the hasidic storytellers." "Telling parables, explains Rabbi Wineman, was a strategy that the hasidic masters used to foster a radical shift in thinking about God, the world, and the values and norms of religious life. Although these parables date back 200 years or more, they deal with moral and religious themes and issues still relevant today. Each is accompanied by notes and commentary by the author that illuminate their ideological significance and their historical roots and background."